Islandsk fraseologi: ordforbindelser i Íslensk Orðabók - Hallsteinsdóttir, Erla; Quasthoff, Uwe (LexicoNordica, 2009)
After a short overview over research on Icelandic phraseology, this article focuses on the lexicographic description of phraseological units in the monolingual Icelandic dictionary Íslensk Orðabók. We analyse both the printed and the electronic version of the dictionary, whereby several questions are addressed: What is the objective of the dictionary? Who are the intended dictionary users and how are their needs fulfilled? How can the lexicographic description be optimised? What linguistic sources are available and how can they be used? What are the perspectives of the dictionary? The article draws a picture of a dictionary at crossroads: substantial conceptual – lexicographic and financial – key decisions concerning its future await clarification.